Coronary Endarterectomy with off Pump Coronary Artery Bypass Surgery- A Review (Cardiovascular Journal, 2017)
Coronary endarterectomy is first described as an alternative surgical procedure for myocardial revascularization against diffuse coronary artery disease by Baily et al. in 1956. Coronary endarterectomy provides complete surgical revascularization of the myocardium in diffuse and calcified coronary arteries with adequate blood flow to distal part of occluded arteries, thus improving ventricular function. However, the initial outcomes of coronary endarterectomy were not satisfactory but now-a-days different studies have shown that coronary endarterectomy with coronary artery bypass grafting can be done safely with acceptable morbidity and mortality. Moreover, the graft patency rate on angiographic evaluation is also good following coronary endarterectomy. So, its time to reevaluate this old techniques, and reanalysis the current outcomes of coronary endarterectomy and readdress its indication in diffuse coronary artery diseaseCardiovasc. j. 2017; 10(1): 84-90